2018
DOI: 10.1111/modl.12493
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Intersection Between Teachers’ Beliefs and Research Findings in Pronunciation Instruction

Abstract: This study explored teachers’ beliefs about pronunciation instruction in Spanish as a second language (L2). An online survey was used to collect data from 100 participants, grouped into 4 categories based on their previous training in principles and methods of pronunciation instruction. This article reports results from 15 survey items which covered participants’ beliefs regarding 6 major themes: the importance of pronunciation, how pronunciation develops, when to teach it, what to teach, how to teach, and who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 83 publications
(128 reference statements)
1
27
0
2
Order By: Relevance
“…Despite this shift, Huensch () found a tension in the survey responses of instructors who simultaneously prioritized intelligible speech but also valued native‐like accuracy. Similarly, Nagle et al () reported that while Spanish instructors generally disagreed with a survey item that stated “only individuals with nativelike Spanish pronunciation should teach it,” this item simultaneously had the highest variability on the survey, demonstrating some instructors’ upheld nativeness principles (p. 15). Missing from these studies is direct evidence of which pronunciation features are targeted in foreign language classrooms and the extent to which pronunciation instruction and corrective feedback prioritize nativeness and intelligibility.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this shift, Huensch () found a tension in the survey responses of instructors who simultaneously prioritized intelligible speech but also valued native‐like accuracy. Similarly, Nagle et al () reported that while Spanish instructors generally disagreed with a survey item that stated “only individuals with nativelike Spanish pronunciation should teach it,” this item simultaneously had the highest variability on the survey, demonstrating some instructors’ upheld nativeness principles (p. 15). Missing from these studies is direct evidence of which pronunciation features are targeted in foreign language classrooms and the extent to which pronunciation instruction and corrective feedback prioritize nativeness and intelligibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MacDonald's () interviews with eight ESL instructors in Australia revealed that participants viewed pronunciation instruction as peripheral and only needing attention if/when students had difficulties. In their survey of Spanish instructors, Nagle et al () found that instructors valued both proactive and reactive approaches to teaching pronunciation. In the Canadian ESL context, classroom observation data from Foote et al () indicated that 67–93% of pronunciation episodes were incidental, with a majority of those that were preplanned coming from a single tongue‐twister activity (p. 190).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another body of work has examined the extent to which phonetics instruction facilitates gains in pronunciation, as determined by listener ratings or through acoustic comparison of learner productions to a native speaker baseline (e.g., Kissling, 2013;Lord, 2005Lord, , 2008. In her survey of Spanish FL instructors, Huensch (2019) observed a tension in instructors' responses, insofar as they seemed to prioritize intelligible speech as an important learning goal while also valuing nativelike accuracy (see also, Nagle et al, 2018). On the one hand, an emphasis on accentedness in the literature and in the classroom can be important given that more accented speech may be perceived as less grammatical (Ruivivar & Collins, 2018) and may be associated with negative evaluations of intelligence, successfulness, and other markers of social status (Fuertes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sie wurden alle in den USA durchgeführt. Nagle, Sachs & Zárate-Sández (2018) befragen Spanischlehr-kräfte zum Ausspracheunterricht. Huensch (2018, 2019 untersucht die Wahrnehmungen und Überzeugungen von Lehrkräften, die Deutsch, Spanisch und Französisch unterrichten.…”
Section: Wahrnehmung Im Ausspracheunterricht Anderer Fremdsprachenunclassified